Histories of Transnational Crime
XIII, 188 p. 1 illus.
Keywords: In the past two decades, the study of transnational crime has developed from a subset of the study of organized crime to its own recognized field of study, covering distinct societal threats and requiring a particular approach. This volume provides examples of transnational crime, and places them in a broad historical context, which has so far been missing from this field of study. The contributions to this comprehensive volume explore the causes and historical precursors of six main types of transnational crime: piracy human smuggling arms trafficking drug trafficking art and antique trafficking corporate crime The historical contributions demonstrate that transnational crime is not a novel phenomenon of recent globalization and that, beyond organized crime groups, powerful individuals, governments and business corporations have been heavily involved. Through a systematic historical and contextual analysis of thesetypes of transnational crime, the contributions to this volume provide a fundamental understanding of why and how various forms of transnational crime are still present in the contemporary world.